El sistema de cargos en San Antonio de las Huertas como instancia integradora de la vida social - Korsbaek, Leif; González Ortiz, Felipe; García Martínez, Emilio; García Hernández, Juan Carlos; Emeterio Ponciano, Juan; Limas Ruiz, Lorena; Zarza Barranca, Lucía; Morelos Salazar, Mauricio; Antonio Julián, Víctor (CIENCIA ergo-sum; Vol. 5 Núm. 3 (1998): CIENCIA ergo-sum (noviembre 1998-febrero 1999), 2017)
-